Nilai-Nilai Al-Qur’an Dalam Tradisi Mapacakke’ Di Desa Pangalli, Kecamatan Walenrang Timur, Kabupaten Luwu - Siti Hardianti Rukmana; Achmad Abubakar; Ahmad Mujahid (Program Pascasarjana, UIN Alauddin Makassar, 2026)
This article examines the Mapacakke’ tradition, which is alive and practiced by the community of Pangalli Village as part of their religious and social expressions in daily life. This study aims to uncover the values of the Qur’an contained within it. The research employs a qualitative method with a phenomenological approach, which seeks to understand the meaning of the tradition as experienced, believed, and interpreted by its practitioners. Data were collected through observation, in-depth interviews with religious leaders, traditional leaders, and community members, as well as documentation. The results indicate that Mapacakke’ is understood as a religious-social ritual serving to seek safety, bring inner peace, and strengthen social bonds. Its implementation involves preparation stages, a central ceremony consisting of collective prayer and the sprinkling of water, and a concluding communal meal. This tradition embodies Qur’anic values such as ta‘āwun (mutual aid), syūrāh (consultation), silaturahmi (social bonding), collective dhikr, and the reinforcement of tawhid, which are naturally internalized within the community’s cultural practices. Thus, Mapacakke’ represents the harmonization of local customs and Islamic teachings, and demonstrates how the values of the Qur’an are lived out and actualized within the socio-cultural context of the Pangalli Village community.